Pine Wilt Disease: A Threat to Pine Forests in Turkey? - AKBULUT, Sulyman (2008)
The pinewood nematode, is the causal agent of pine wilt disease, a serious threat to native pine forest in eastern Asia (Japan, Korea, China and Taiwan) and some parts of North America (USA, Canada and Mexico). In 1999, this nematode was found and identified for the first time in Portugal and in Europe. The detection of this quarantine pest in Portugal has indicated the need to know more about the distribution of Bursaphelenchus spp. in coniferous trees in Europe in order to describe the geographic range of the species and to act quickly in case of the nematode’s unwanted introduction into other European regions. Pine forest has a wide distribution in Turkey that increases the number of susceptible host trees for pinewood nematode. Because of these resaons, some regions of Turkey were surveyed for the presence of the nematode. Three different species of Bursaphelenchus were found. However, B. xylophilus was not detected. The detection of B. mucronatus, very similar to B. xylophilus biologically and morphologically, is very important. The presence of this species indicates that B. xylophilus could spread easly in conifer forests of Turkey. A study was conducted to determine the pathogenicity of B. mucronatus and 80% of seedlings of P. sylvestris were wilted. Biological characteristics of M. galloprovincialis were compared with M. carolinensis, Nort American vector, and some of them were found to be similar.